PEMANFAATAN GULMA AIR UNTUK MENINGKATKAN PRODUKSI MIKROALGA Spirulina platensis SEBAGAI PAKAN ALAMI IKAN GURAMI - Christiani Christiani; Titi Chasanah; Diana Retna Utarini Sri Rahayu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2013)
Stadium larvae of gourami fish are very sensitive because it has been not adapted well to the environment and their digestive system is also not perfect yet. Larvae do not have the stomach and their enzymatic activity is not optimal, so need a natural food in sufficient quantities. Proper feed formulation in addition to cost saving fish farmers are also desperately needed this study aims to determine the effect of Spirulina microalgae as a natural food with different weight and time of feeding on the growth and sustainability of gourami fish and to determine the formulation of a good natural food for fish larvae. This research used an experimental method with Split Plot Design in 3 times replication for each treatment combination microalgae cell concentrations as mainplot tested: 0, 50, 100, 150% of body weight and as a sub-plot was time of feeding: 1, 2 and 3 times per day. The results showed a feed formulations of Spirulina microalgae with different weight and timing of an effect on the growth of larvae compared with the control (giving Tubifex) and a natural feeding weighing 100% of body weight with a feeding time of 1 or 2 times to generate growth and survival of carp larvae Keywords: Spirulina platensis, weight, time of feeding, the larvae